Unique pits on the erythrocytes of the lesser mouse-deer, Tragulus javanicus - Fukuta, Katsuhiro; Kudo, Hiroshi; Syed Salim, Syed Jalaludin (Wiley-Blackwell Publishing, 1996)
The lesser mouse-deer, Tragulus javanicus, is the smallest living ungulate and it possesses the smallest erythrocytes amongst mammalian species. We observed pits on its erythrocytes by scanning electron microscopy. They were 68-390 nm in diameter (135 ± 65 nm) and appeared in 12.8% of erythrocytes examined. They represent unique structures that have not previously been reported physiologically or pathologically.